Classification of Makasar Fruit Extract (Brucea javanica L. Merr.) Based on The Level of Ripeness Using a Combination of FTIR and UV-Vis Spectroscopy with Chemometrics - Charles Banon; Deni Agus Triawan; Morina Adfa; Monica Santa Ana Sihite; Ria Nurwidiyani; Widia Rahmi (Jurnal Kimia Sains dan Aplikasi, 2023)
Makasar fruit (Brucea javanica L. Merr) is a medicinal plant frequently utilized in Indonesia for its anti-malarial, anti-diabetic, antioxidant, and antibacterial properties. This research aims to classify extracts from B. javanica fruits based on their ripeness levels using a combination of FTIR and UV-Vis spectroscopy with chemometrics. Makasar fruits were extracted using methanol assisted by ultrasonic technology, resulting in a higher yield of extract from ripe fruit (black in color) than unripe fruit (green in color). The FTIR spectrum was measured at wavenumbers ranging from 4000 to 600 cm-1, while the UV-Vis spectrum was measured at wavelengths ranging from 200 to 800 nm. Notably, the UV-Vis spectrum revealed absorption peaks at 206 nm, attributed to the quassinoid group, and 265 nm, associated with the flavonoid group. Simultaneously, the FTIR spectrum showed various functional groups, including O-H, C-H, δ-lactone, C=C aromatic stretching vibrations, and C-O-C bending vibrations. Before conducting chemometric analysis, the FTIR and UV-Vis spectra were pre-processed as baseline and SNV. The research findings demonstrate that by employing UV-Vis and FTIR spectra in combination with chemometrics, it has been possible to distinguish Makasar fruit according to its ripeness level. Ripe and unripe fruit extracts were grouped with PC values of 88% for UV-Vis and 90% for FTIR, indicating distinct profiles between ripe and unripe fruit extracts of Brucea javanica.